Self-Identified Employment Challenges for Young Adults with a Cleft Lip and Palate: A Qualitative Exploration - Haslina Rani; Hasherah Mohd Ibrahim; Nurshazwanie Amira Mohamed Noor Shafie; Suziyani Mohamed; Azianura Hani Shaari; Murshida Marizan Nor; Tuti Ningseh Mohd-Dom (Behavioral Sciences)
As individuals with a cleft lip and palate (CLP) transition into adulthood, they face unique employment challenges related to income, job stability, and fewer career options. This study explored these challenges through two focus group discussions with 19 participants (aged 21–38), primarily women, to understand their employment experiences. Thematic analysis revealed the following three main themes: (1) physical factors, (2) psychosocial factors, and (3) overcoming employment challenges, with nine sub-themes including speech, hearing, appearance, health, childhood experiences, societal expectations, lack of self-confidence, communication improvement, and self-esteem building. The findings highlighted that physical and psychosocial factors significantly shape employment outcomes for CLP individuals. Difficulties with speech often hinder professional communication, while appearance concerns can reduce confidence in interviews and workplaces. To address these issues, the participants used strategies like targeted speech therapy and self-esteem building, which helped improve their communication and resilience. This study emphasises the need for targeted interventions such as specialised career counselling, access to assistive technologies, and inclusive workplace policies to support CLP individuals in overcoming employment barriers and achieving stable careers.